Integration of AI and iOS API: how to use Core ML, Vision, SiriKit in applications - Vdovenko, Dmytrii; Seidykh, Olga (My University, 2025)
The integration of native APIs for AI opens up opportunities for creating adaptive, secure, and productive iOS applications. Core ML, Vision, and SiriKit form the basis of modern intelligent systems that run locally and preserve user privacy. Інтеграція нативних API для ШІ відкриває можливості для створення адаптивних, безпечних і продуктивних додатків для iOS. Core ML, Vision і SiriKit складають основу сучасних інтелектуальних систем, які працюють локально і зберігають конфіденційність користувачів.
Keywords: mobile technologies; intelligent systems; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; мобільні технології; інтелектуальні системи